The Effect of the Project-Based Learning (PjBL) Model on Students' Critical Reasoning and Learning Achievement in Islamic Education Based on the SDGs - Demes Ilham Al Fikri; Wachidi; Mahasri Shobahiya (Profetika: Jurnal Studi Islam, 2024)
Objective: This research aims to: (1) examine the effect of the PjBL model on improving critical reasoning skills at SDN Masaran 5; (2) analyze the impact of PjBL on enhancing students' learning achievement; and (3) assess the overall effectiveness of PjBL in improving critical thinking and learning outcomes in the context of Islamic Education (PAI) and Character Building (BP), aligned with the Sustainable Development Goals (SDGs), particularly Goal 4: Quality Education. Theoretical framework: In the era of 21st-century education, the development of students' 4C skills—Communication, Collaboration, Critical Thinking, and Creativity—is a fundamental necessity. Within this framework, Project-Based Learning (PjBL) emerges as a powerful pedagogical model that fosters student engagement, innovation, and critical reasoning through meaningful projects. Literature Review: Project-based learning fosters critical thinking and academic achievement, especially in Islamic education, by promoting active learning aligned with SDGs to support holistic, student-centred, and values-based education. Methods: Grounded in constructivist learning theory, this study adopts a mixed-methods approach, combining qualitative and quantitative methods. The research design consists of Classroom Action Research (CAR) and Pre-Experimental Research using the One Group Pre-Test and post-test Design. The sample includes 18 fourth-grade students, selected through total sampling. Data collection techniques include observation for the qualitative phase and pre-test/post-test instruments for the quantitative phase. Results: The results reveal that the PjBL model significantly improves students’ critical reasoning skills. Furthermore, it effectively enhances learning achievement in PAI and BP subjects. The integration of Islamic values within student-centred projects not only enriches content understanding but also aligns the educational process with the values of the SDGs, promoting holistic, inclusive, and transformative learning. Implications: This study has important implications for educators and policymakers, highlighting the need for innovative instructional models that blend faith-based education with global education goals. Novelty: The novelty of this research lies in its focus on implementing PjBL within Islamic Education, framed through the lens of sustainable development. It offers a replicable model for primary-level instruction that supports both cognitive and character development in line with SDG aspirations.